2019
DOI: 10.1080/19359705.2019.1568946
|View full text |Cite
|
Sign up to set email alerts
|

Multiple minority stress: The role of proximal and distal stress on mental health outcomes among lesbian, gay, and bisexual people of color

Abstract: There is minimal research addressing the mental health outcomes of lesbian, gay, and bisexual people of color (LGB-POC). Meyer's (2003; 2015) minority stress theory posits that the manifestation of depression and anxiety symptomology is due to the excess distal and proximal stress that minority groups face because of their societal marginalization. The purpose of this study was to determine the predictive value of distal stress measures (e.g. LGBT-POC microaggressions and daily heterosexist/racist experiences)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
90
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 77 publications
12
90
0
2
Order By: Relevance
“…As this study was conducted in 2017, it could be assumed that the stress of Korean SMW was elevated when they encountered negative remarks about homosexuality during the Korean presidential election campaign [ 50 ]. Moreover, some previous studies pointed out the role of distal stress [ 3 , 49 ] when, for example, frequent exposure to negative media messages about sexual minorities were associated with greater psychological distress [ 2 ]. The results of our study showed that even if discrimination was not experienced physically, hearing that others were being discriminated against could impact mental health in the same way as experiencing it firsthand.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As this study was conducted in 2017, it could be assumed that the stress of Korean SMW was elevated when they encountered negative remarks about homosexuality during the Korean presidential election campaign [ 50 ]. Moreover, some previous studies pointed out the role of distal stress [ 3 , 49 ] when, for example, frequent exposure to negative media messages about sexual minorities were associated with greater psychological distress [ 2 ]. The results of our study showed that even if discrimination was not experienced physically, hearing that others were being discriminated against could impact mental health in the same way as experiencing it firsthand.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point when describing the health of SMW is the difference between inner groups. In previous studies, bisexual women reported poorer health than lesbians [ 1 , 3 , 15 , 22 , 23 ]. However, most of these findings were reported in Western countries [ 11 , 12 , 13 , 14 , 15 , 21 ].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations